A Simple Snowfall Retrieval Algorithm for the GPM Dual‐Frequency Precipitation Radar: Development and Validation With OLYMPEX Campaign Observation - S. Akiyama; S. Shige; K. Aonashi; T. Iguchi (Earth and Space Science)
Abstract The current operational algorithm for the Ku‐ and Ka‐band Dual‐frequency Precipitation Radar (DPR) onboard the Global Precipitation Measurement (GPM) satellite, which does not effectively utilize Ka‐band radar, underestimates snowfall amount. We developed a dual‐frequency method (DF‐method) that can be incorporated into the framework of the DPR operational algorithm. Estimates from the DF‐method, as well as those from the operational algorithm, were validated against data nearly simultaneously measured by in situ airborne instruments and those from a ground‐based radar during the Olympic Mountains Experiment (OLYMPEX). The results showed the DF‐method produced high correlation, but some bias dependent on an assumed particle model. Both the operational algorithm and the DF‐method using the scattering properties of the spheroid model equivalent to the best aggregate model yielded unsatisfactory results, indicating that it is important to use realistic snow scattering properties in the DF‐method, rather than relying on the Mie or T‐matrix scattering.